The art of Kelantan traditional pottery: the limitations and way forward. - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (Universiti Kebangsaan Malaysia (UKM), Bangi, Selangor., 2013)
The traditional pottery of Kelantan is not only known for unique forms and techniques, but also the realistic aesthetic pottery traditional concept of art in Malay. These have led to an increasing demand for Kelantan pottery wares. Hence, this paper seeks to illuminate on the traditional pottery of Kelantan state in Malaysia. The paper investigates and reviewed the history of Malay pottery down to Kelantan pottery, and also analysed the techniques and processes used in Kelantan traditional pottery production. This was achieved by first visiting three traditional pottery centres in Kelantan. The outcome of the visit revealed how Kelantan potters create models by hand turning or carving the concepts in plaster (POP) using turning wheel. Also, from the information gathered, the paper reviewed the production process from the conceptualisation stage to realisation stage, highlighted the limitations of the method and finally proposed a way forward. The proposed way forward (digital and rapid technology) was then tested to know it’s viability by using it to develop a product. The findings from this revealed that digital and rapid technology is a viable tool for reducing development time, enhancing prototype quality (accuracy), preventing material wastage, producing exclusive designs and durable prototypes, however, the research shows that rapid prototyping is an expensive approach.